DEATH, NATIONALISM, LANGUAGE AND REVOLT IN J. M. SYNGE AND WOLE SOYINKA - A THEMATIC STUDY (1990)
This thesis examines four themes in the plays of J.W. Synge and Wole Soyinka - namely, death, nationalism, language and revolt - to represent the multiple aspects of convergence and divergence which a combined reading of their works reveals, and to appreciate the sensibilities, the social contexts and the significance (local and universal) of both writers. It is divided into six chapters: Chapter One: Introduction; Chapter Two: Death in J.M. Synge and Wole Soyinka (Tharatomimesis and Thanatodicea Examined); Chapter. Three: J.M. Synge, Wole Soyinka and the National Question; Chapter Four: Language: The Synge and Soyinka Experience; Chapter Five: Modernism and the Theatre of Revolt: J. W. Synge and Wole Soyinka; Chapter Six: Conclusion. The thesis advances four main propositions, viz: (a) Synge and Soyinka express an abiding concern about the centrality of death in human experience; man, both writers contend, is, in the midst of life, in death; hence, they paint an artistic landscape in which the individual urge to assert itself is often subverted by the reality or the threat of death, thus giving vent to the idea that death is the ultimatum of life. (b) Both writers have been dismissed as a-national in their respective countries, not just because they are incapable of political thought, as has been alleged in Synge's case, or unpatriotic, as alleged in both cases, but because of their refusal to embrace the reductionist and exclusivist literary dogma preached by the ultra-nationalists in their societies. Both of them advocate the freedom of the creative instinct from ideological fetters and assign themselves the task of desecrating the sacred gods of their time with the belief that truth, as opposed to flattery, should be the oyster of art; and it is perhaps this critical detachment and objectivity that constitutes true nationalist writing. (c) Synge and Soyinka, like many writers, accord language a pre-eminence in their scale of artistic tools; of particular interest is their foregrounding of language; that is, the fluency with which their language attains performative dimensions and generates visual and aural impulses, and the implications of this for the theatrical communication of their plays. (d) A search for the root of both writers' sensibility must be traced, in part, to the modernist temperament of their works manifest not only in their 'avantgarde' utilisation of language but more contextually in their revolt against preconceived existential and social notions and ethos. In sum, this thesis attempts to give intimations of the individual genius of both writers, situate them within their social and historical contexts, and assess their universal value; the parallels between them are highlighted but their differences are not overlooked. On the whole, however, this exercise can represent only the beginning of a more complex discussion of both writers, particularly with regards to their backgrounds: the Anglo-Irish National Theatre Movement and the Modern Nigerian Theatre of the pre-Independence and post-Independence eras.